2017
DOI: 10.1103/physreva.96.033833
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum noise reduction in intensity-sensitive surface-plasmon-resonance sensors

Abstract: We investigate the use of twin-mode quantum states of light with symmetric statistical features in their photon number for improving intensity-sensitive surface plasmon resonance (SPR) sensors. For this purpose, one of the modes is sent into a prism setup where the Kretschmann configuration is employed as a sensing platform and the analyte to be measured influences the SPR excitation conditions. This influence modifies the output state of light that is subsequently analyzed by an intensity-difference measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 82 publications
0
43
0
Order By: Relevance
“…However, the role of pure phase damping is not completely negligible. Our work shows that both amplitude and pure phase damping can lead to decoherence in quantum plasmonic systems, and it provides useful information about the loss of coherence that should be considered when designing plasmonic waveguide systems for phase-sensitive quantum applications, such as quantum sensing [20][21][22][23] and quantum imaging [23,24]. The techniques developed here for characterising decoherence in plasmonic waveguides may be useful for studying other plasmonic nanostructures, such as those used as nanoantennas [4], as unit cells in metamaterials [63,64] and as nanotraps for cold atoms [65].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the role of pure phase damping is not completely negligible. Our work shows that both amplitude and pure phase damping can lead to decoherence in quantum plasmonic systems, and it provides useful information about the loss of coherence that should be considered when designing plasmonic waveguide systems for phase-sensitive quantum applications, such as quantum sensing [20][21][22][23] and quantum imaging [23,24]. The techniques developed here for characterising decoherence in plasmonic waveguides may be useful for studying other plasmonic nanostructures, such as those used as nanoantennas [4], as unit cells in metamaterials [63,64] and as nanotraps for cold atoms [65].…”
Section: Introductionmentioning
confidence: 88%
“…These nanophotonic devices are important for emerging quantum technologies, such as photonic-based quantum computers [16,17] and quantum communication networks [18]. Following on from early work probing SPPs with quantum states of light, such as entangled photons [19], recent studies have demonstrated several key quantum applications, including quantum sensing and imaging [20][21][22][23][24], quantum spectroscopy [25], quantum logic gates [26], entanglement generation [27] and distillation [28], and quantum random number generation [29]. What is surprising is that all of these applications can be realized even in the presence of loss, which is always present in plasmonic systems as they are scaled down to confine light to smaller scales.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the fiducial photon number distributions we introduce here would be useful for an operating regime of a parameter that is locally calibrated in advance, so the identification of minute changes of the parameter is only of interest. That is, fortunately, often the case, e.g., for plasmonic sensors [36,37] or phase tracking [38]. In such cases, the validity of the quantum Cramér-Rao bound can be investigated in terms of the required minimum number of measurements and the minimum prior knowledge of the parameter [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For our sensor to be understood in the context of transmission spectroscopy we treat the actual reflection of a single photon from the ATR setup as a transmission through the ATR setup, as in Ref. [26]. The generation of the single-photon state (the signal) is heralded by a detection of its twin photon (the idler), due to the quantum correlation of photon pairs initially produced via spontaneous parametric down conversion (SPDC).…”
Section: Introductionmentioning
confidence: 99%